The Puzzle of ‘Unspent’ Funds in Italy’s European Social Fund - Christine Lutringer (Revue Internationale de Politique de Développement)
This chapter focuses on the spending dynamics around one of the largest social funds globally: the European Social Fund (ESF). More specifically, it explores the institutional conditions and the tensions around its use/lack thereof in Italy, one of the largest recipients of the Fund. While financial execution does not subsume the effective implementation or the effectiveness of the activities that are funded, the chapter suggests that it is a key marker in the policy debate in Italy, and seeks to analyse the terms of this debate by placing it in its institutional and financial context, in particular against the backdrop of reforms enacted at both the European Union (EU) and the domestic level. It argues that late spending is not only a marker of a series of institutional blockages, it also reveals a specific mode of governance that is shaped at the same time by national, regional and supranational institutions, norms, and interests as well as by flows of funds and ideas that converge and materialise in a variety of administrative, political and financial practices.